CycloSiFA: the next generation of silicon-based fluoride acceptors for positron emission tomography (PET): dedicated to Professor Manfred T. Reetz on the occasion of his 80th birthday - Mawick, Matthias; Jaworski, Carolin; Bittermann, Jens; Iovkova, Ljuba; Pu, Yinglan; Wängler, Carmen; Wängler, Björn; Jurkschat, Klaus; Krause, Norbert; Schirrmacher, Ralf (Angewandte Chemie. International edition, 2023)
The ring-opening Si-fluorination of a variety of azasilole derivatives cyclo-1-(iPr2Si)−4-X−C6H3−2-CH2NR (4: R=2,6-iPr2C6H3, X=H; 4 a: R=2,4,6-Me3C6H2, X=H; 9: R=2,6-iPr2C6H3, X=tBuMe2SiO; 10: R=2,6-iPr2C6H3, X=OH; 13: R=2,6-iPr2C6H3, X=HCCCH2O; 22: R=2,6-iPr2C6H3, X=tBuMe2SiCH2O) with different 19F-fluoride sources was studied, optimized and the experience gained was used in a translational approach to create a straightforward 18F-labelling protocol for the azasilole derivatives [18F]6 and [18F]14. The latter constitutes a potential clickable CycloSiFA prosthetic group which might be used in PET tracer development using Cu-catalysed triazole formation. Based on our findings, CycloSiFA has the potential to become a new entry into non-canonical labelling methodologies for radioactive PET tracer development.
Online veröffentlicht: 18. Oktober 2023
Gesehen am 29.07.2024
Keywords: Festschrift